THE CLINICAL PHARMACOLOGY OF HEPATOTROPIC DRUGS - Bychkova, О. Yu.; Savchenko, V. M.; Tomina, O. Е.; Kartvelishviliy, A. Yu. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Clinical pharmacology of hepatotropic drug in the international system of ATC (anatomic-therapeutic-chemical) drugs classification is described. The classification, pharmacokinetics and pharmacodynamics characteristics, indications and principles of using drugs from this group in a therapeutic clinic are represented. Are considered Contraindications, side effects and interactions with other hepatotropic drugs are considered.